Sacrifice and national belonging in twentieth-century Germany - Funck, Marcus; Eghigian, Creg (The Walter Prescott Webb memorial lectures, 2002)
German sacrifice today / John Borneman -- The meaning of dying / Marcus Funck -- Was it all just a dream / Brian E. Crim -- Injury, fate, resentment, and sacrifice in German political culture, 1914-1939 / Greg Eghigian -- There is a land where everything is pure / Michael Geyer -- The violence of difference / Uli Linke -- Sacrifice and victimization in the commemorative practices of Nazi genocide after German unification memorials and visual metaphors / Silke Wenk